Mutations in HECW2 are associated with intellectual disability and epilepsy. Issue 10 (22nd June 2016) - Halvardson, Jonatan; Zhao, Jin J; Zaghlool, Ammar; Wentzel, Christian; Georgii-Hemming, Patrik; Månsson, Else; Ederth Sävmarker, Helena; Brandberg, Göran; Soussi Zander, Cecilia; Thuresson, Ann-Charlotte; Feuk, Lars
Abstract : Background: De novo mutations are a frequent cause of disorders related to brain development. We report the results of screening patients diagnosed with both epilepsy and intellectual disability (ID) using exome sequencing to identify known and new causative de novo mutations relevant to these conditions. Methods: Exome sequencing was performed on 39 patient–parent trios to identify de novo mutations. Clinical significance of de novo mutations in genes was determined using the American College of Medical Genetics and Genomics standard guidelines for interpretation of coding variants. Variants in genes of unknown clinical significance were further analysed in the context of previous trio sequencing efforts in neurodevelopmental disorders. Results: In 39 patient–parent trios we identified 29 de novo mutations in coding sequence. Analysis of de novo and inherited variants yielded a molecular diagnosis in 11 families (28.2%). In combination with previously published exome sequencing results in neurodevelopmental disorders, our analysis implicates HECW2 as a novel candidate gene in ID and epilepsy. Conclusions: Our results support the use of exome sequencing as a diagnostic approach for ID and epilepsy, and confirm previous results regarding the importance of de novo mutations in this patient group. The results also highlight the utility of network analysis and comparison to previous large-scale studies as strategies to prioritise candidate genes for further studies. This study adds knowledge to the increasingly growing list of causative and candidate genes in ID and epilepsy and highlights HECW2 as a new candidate gene for neurodevelopmental disorders.